Regional risksharing and redistribution in the German federation - Jürgen von Hagen; Ralf Hepp (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2000)
We provide empirical estimates of the risksharing and redistributive properties of fiscal equalization among the states of the German federation. Fiscal equalization serves as a mechanism to insure state budgets against asymmetric revenue shocks, but provides almost no insurance against regional income shocks. Equalization responds only weakly to income differentials but strongly to tax revenue differentials across states. A further result is that the correlation of state tax revenues with state GDPs has declined over time. This may reflect a weakening in state tax efforts in response to the adverse incentive effects of fiscal equalization.
Keywords: 330; Regional Risk-sharing; Fiscal Federalism; Monetary Union; Horizontaler Finanzausgleich; Steueraufkommen; Länderhaushalt; Regionaler Konjunkturzyklus; Schock; Risi